The Evolution of the Emotion-Processing Mind. - Langs, Robert (Karnac Books, 1996)
In attempting to unify psychoanalytic and evolutionary theories, Langs offers a concise account of the most current versions of Darwinian and neo-Darwinian theory. He then develops the argument that the emotion processing mind is an organ of adaptation that has evolved by natural selection.